PENERAPAN SIMULASI ALAT UKUR PENDETEKSI KELEMBAPAN TANAH MENGGUNAKAN PERANGKAT MIKROKONTROLER ARDUINO UNO - Muhammad Ridwan Efendi; Mohammad Narji (Fakultas Ilmu Komputer dan Desain - Unsurya, 2020)
Measurement is very important in the world of science, especially in engineering. Measurement in engineering is used as a protection system or control system for a process. Measurements play an important role in helping human work and provide the convenience of technicians in determining the value of a quantity or variable. The measurement in question is to determine soil moisture. Because by knowing the soil moisture accurately, it affects the sustainability of plants planted on the soil. Considering that this measurement is very important, it is necessary to have a measuring instrument that can detect soil moisture accurately so that healthy plants can be produced, as expected. For this research, we intend to make a measuring instrument for detecting soil moisture using an Arduino Uno microcontroller device. In this research method, the stages of the research will be described as the system development method, research location, and data collection techniques. The results of this study are the reading of the sensor value is wet, moist and dry in accordance with a predetermined Analog Data range value. Namely Wet conditions when getting output with a lower limit range of 150 and upper limit 339, humid conditions when getting output with a lower limit range 340 upper limit 475, Dry conditions when getting a sensor value with a lower limit range is 476 and upper limit 1023.Â Keywords: Application of Simulation, Humidity Detection, MicrocontrollerÂ